The impact of management accounting practices: Comparative analysis study between Jordan and Romania - Omar ALHATO (Theoretical and Applied Economics, 2023)

(untitled)
The most topical twenty years ago in the 20th century; there has been a development of accounting research in rising economies. Research in management accounting takes very diverse academic perspectives; this may be embedded in a mass of compound factors, including the increasing pressures of globalization, technological advancements, and the business volumes of enterprises that have enlarged and developed significantly. Moreover, this paper gives further exact proof of the utilization of managerial accounting techniques. Specifically, it provides a focused analysis of management accounting research published in recent years. The core intention of this paper is to present an overview of some of the recent management accounting literature. With respect to the use of managerial accounting in Middle East nations in the case of Jordan and compared to Romania.